2010
DOI: 10.1103/physrevb.81.235407
|View full text |Cite
|
Sign up to set email alerts
|

Finite-bias electronic transport of molecules in a water solution

Abstract: The effects of water wetting conditions on the transport properties of molecular nanojunctions are investigated theoretically by using a combination of empirical-potential molecular-dynamics and first-principles electronic-transport calculations. These are at the level of the nonequilibrium Green's-function method implemented for self-interaction corrected density-functional theory. We find that water effectively produces electrostatic gating to the molecular junction with a gating potential determined by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 44 publications
3
59
0
Order By: Relevance
“…For instance, the confirmation assumed by DNA double helices is itself determined by the extent to which the molecules are surrounded by water and by the energy associated with hydration. Additionally, as shown recently by Rungger et al, 56 in molecular junctions, solvation by water effectively produces electrostatic gating which can change the average alignment of the molecular energy levels with respect to the leads E F . Finally, around room temperature the thermal motion of water molecules can produce rapidly fluctuating local dipolar fields that, in turn, lead to fluctuations in the energy-level positions of individual molecular orbitals on the DNA.…”
Section: Solvent Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the confirmation assumed by DNA double helices is itself determined by the extent to which the molecules are surrounded by water and by the energy associated with hydration. Additionally, as shown recently by Rungger et al, 56 in molecular junctions, solvation by water effectively produces electrostatic gating which can change the average alignment of the molecular energy levels with respect to the leads E F . Finally, around room temperature the thermal motion of water molecules can produce rapidly fluctuating local dipolar fields that, in turn, lead to fluctuations in the energy-level positions of individual molecular orbitals on the DNA.…”
Section: Solvent Effectsmentioning
confidence: 99%
“…This is similar to what found for benzene molecules attached to gold via thiol groups. 56 Furthermore, the HOMO and LUMO energies fluctuate about the mean value with a standard deviation of 0.36 eV and 0.28 eV, respectively. It is worth noting that although the peak of the histogram for the HOMO level in the presence of the solvent is ϳ1.5 eV lower than the HOMO level in vacuum, energies near the right edge of the histogram are relevant for the observed I-V characteristics.…”
Section: Solvent Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work functions of EuO and Cu are calculated by using the Hartree electrostatic potential, V H , as the reference potential. 41 We define W Cu as the difference between E F and the vacuum potential V vacuum of a Cu slab, while W EuO is given by the difference between V vacuum and the energy of the valenceband top of a EuO slab, V VB . We calculate W Cu = 3.9 eV, which is somewhat lower than the theoretical values, ranging between 4.5 to 5.3 eV, 42 and the experimental value of about 4.65 eV.…”
Section: Spin Transport Properties Of the Euo Junction At Zero Biasmentioning
confidence: 99%
“…Furthermore, additional fluctuations may arise from the electrostatic gate action introduced by the solvent molecules. 5,6 In order to overcome these intrinsic difficulties, it was further suggested to trace the current fluctuations as the ssDNA is translocated across the pore, and to use their statistical distribution in order to unambiguously recognize the electronic signatures of the various nucleobases. [7][8][9] Experimentally, Tsutsui et al showed that it is possible to identify single nucleotides in solution by two-probe tunneling current measurements and a thorough statistical analysis of the time-resolved current.…”
Section: Introductionmentioning
confidence: 99%